Vento: dispositivo reductor de velocidad vial, generador de confort en el conductor (2020)
This project is motivated by the interest of generating a better way of driving and road safety, on the different roads of the city of Bogotá, however, taking into account causes and consequences of the location of the different road reducers, despite the fact that they comply with Its function (reducing speed) has an effect on the vehicle due to its startles if it is not passed correctly, even without the need to go faster than the established norm, including all types of vehicles (cars and motorcycles), making these elements uncomfortable for the driver, since when driving when going at high speeds, the energy increases and with this the passage through the reducers affects the vehicle to a greater degree (El tiempo, 2018). This means that one of the parts of the car that gets the most damage is the tires and shock absorbers, the effect called "material stress" is created when passing through a reducer that damages the fibers of the rim, creates bubbles and deteriorates the shock absorbers ( Sierra, 2018). The current road devices that limit the speed of the vehicle to enter different urban areas, including their intersections, are taken into account as alternatives for urban mobility control, in order to generate road safety and thus create configurations on the road and adapt to the cultural behavior of the driver, which is to reduce speed according to established regulations. Consequently, drivers establish their speed according to the implementation of different elements that modify the space of the road, which are due to: pavement wear, traffic signs, gaps, speed bumps, over jumps, among others, this document aims to disclose how by means of industrial design a strategic tool is generated that reduces speed effectively, benefiting it with a driver that complies with the regulations, avoiding damage to the vehicle. For this, an analysis of benchmarks in terms of ways to reduce speed in other areas of study outside the roads, and a research analysis of the Manual of Speed Pacifiers on urban roads, accompanied by the regulations of the Ministry of transport, and the 2017-2026 District Road Safety Plan called zero vision in order to apply industrial design methods taking into account the requirements established by each standard goes and law. This is involved in the Gui Bonsiepe Project Process Process methodology where the step by step is carried out from the root of the problem to the design of the final prototype.